Professionalism Of Islamic Religious Education Teachers In Improving The Quality Of Learning - Wijaya, Fatikh Candra; Munawir, Munawir; Devy, Bilqis Soraya (Jurnal Hadratul Madaniyah, 2025)
The author wrote an article with the title “Professionalism of Islamic Education Teachers (PAI) in Improving the Quality of Learning” because he wanted to know how to become a professional teacher, especially Islamic Education Teachers (PAI) in improving the quality of learning, what things a teacher must master in order to carry out his professionalism well, what strategies PAI teachers apply to improve the quality of learning, the challenges faced by PAI teachers in improving their professionalism, and how the solution to overcome all these problems. This research topic is important to raise because it shows that being a teacher is not just being a teacher, but a teacher must have various competencies that must be met so that it can be said to be a professional teacher. Education needs professional teachers to improve the quality of learning and create better learning experiences. Teachers not only have the task of communicating knowledge to students, but also play a role in designing their personality, morality, and skills to meet the needs of the times. This research is a qualitative study using the literature review method, in which data is collected from various journals, articles, books, and other relevant reading sources.